Conductivity enhancement of Al- and Ta-substituted Li7La3Zr2O7 solid electrolytes by nanoparticles. Issue 3 (March 2022) - Bauer, Alexander; Ali, Md Yusuf; Orthner, Hans; Uhlenbruck, Sven; Wiggers, Hartmut; Fattakhova-Rohlfing, Dina; Guillon, Olivier
Abstract: A nanopowder consisting of La2 Zr2 O7 particles with lithium containing species on their surface was prepared by spray flame synthesis and subsequently added to Li7 La3 Zr2 O12 powder obtained by a conventional solid-state reaction. The spray flame synthesis method utilized in this work yields nanoparticles with a small size of approximately 5 nm, which is unprecedented within the scope of oxide-based ionic conductors for solid-state batteries. Remarkably, the addition of nanoparticles for sintering at a relatively low temperature of 1000 °C significantly improved the ionic conductivity by 50 %. In contrast, there was no influence of incorporating nanoparticles on the conductivity at sintering temperatures at or above 1100 °C, which is the typical temperature range applied for conventional sintering of Li7 La3 Zr2 O12 . Compared to prior published work with analogous materials, a more than twofold improvement in conductivity was demonstrated while the sintering temperature was decreased by 100 °C.